Synergistic Effect of Ramie and Pineapple Fibres Reinforcement on The Strength of Epoxy Matrix Composite - Mercy, J. Lilly; Anand, D Alex; Samrot, Antony V; Rajalakshmi, D.; Shobana, N.; Dhiva, S.; Kasirajan, Kasipandian (International Journal of Membrane Science and Technology, 2023)
Natural fibre reinforced composite of pineapple and ramie fibre unidirectional mats were fabricated through handlayup process and curing through compression molding process. Six samples of the composite material with different combinations of alternating fibres and orientations of the fibre mats were fabricated and tested for their mechanical properties. It was observed that the stacking sequence, type of fibre and orientation of the fibres make a pronounced difference in the mechanical properties. The outer layer of Ramie fibre mat and the 45° orientation of either of the fibres resulted in better mechanical properties. By making a perfect combination of the stacking sequence of the fibres, type of fibres and orientation, it is possible to enhance the properties of the composite.